Cloning, Expression, and Functional Characterization of Autoactivated Human Prethrombin-2 Synthetic Gene by Using Pichia pastoris SMD1168 As a Host - TOTO SUBROTO; WULAN PERTIWI; MUHAMMAD FADHILLAH; KHOMAINI HASAN; OGI BUDIANTORO; SUTARYA ENUS; SOETIJOSO SOEMITRO (Microbiology Indonesia, 2016)
Prethrombin-2 is a thrombin precursor that has important role in blood coagulation. It is the smallest precursor which is activated into thrombin by FXa prior to coagulation process. However, as a commercial theurapetic protein in fibrin sealant component, prethrombin-2 must be activated by ecarin before used. Thus, the production process of this protein needs further purification. In order to eliminate ecarin activation step and to increase production efficiency, we designed, cloned and expressed the recombinant autoactivated human prethrombin-2 in Pichia pastoris SMD1168. The variant was designed with 4 mutations, E40A, D47A, G48P, and E52A, following the result of a previous study. The synthetic variant gene was first optimized to conform with P. pastoris codon preference. The optimized synthetic gene was cloned in pD912 plasmid using XhoI and SacII restriction enzymes. The transformed P. pastoris was selected on agar plate supplemented with 1,000 Âµg.mL-1 Zeocin as a selection marker. This study showed that autoactivated prethrombin-2 was succesfully expressed extracellularly by P. pastoris SMD1168. The activity of recombinant autoactivated prethrombin-2 using a chromogenic substrate S-2238 was 0.540 unit/mg. Taken together, these results demonstrated that autoactivated human prethrombin-2 was successfully produced extracellularly in P. pastoris.